Molecular characterization of the malaria vector Anopheles barbirostris van der Wulp in Sri Lanka - Gajapathy, K.; Jude, P.J.; Goodacre, S.L.; Peiris, L.B.S.; Ramasamy, R.; Surendran, S.N. (Bio Med Central, 2014)
Background: Anopheles barbirostris is a vector of malaria in Sri Lanka. The taxon exists as a species complex in the Southeast Asian region. Previous studies using molecular markers suggest that there are more than 4 distinct clades within the An. barbirostris complex in Southeast Asia. The present study characterizes Sri Lankan An. barbirostris using mtDNA cytochrome oxidase subunit I (COI) and ribosomal RNA internal transcribed spacer 2 (ITS2) gene sequences. Findings: DNA was extracted from morphologically identified An. barbirostris specimens from Sri Lanka, the COI and ITS2 regions amplified and their sequences analysed by comparison with other GenBank entries. Maximum likelihood trees suggested that Sri Lankan An. barbirostris constitute a different molecular type most closely related to clade I. Conclusions: Considering the uncorrected p distances between the clade I and Sri Lankan specimens it is fair to assume that the specimens collected from widely separated locations in Sri Lanka with morphology characteristic of An. barbirostris s.l. form a new molecular type with close resemblance to An. barbirostris s.s from Indonesia and Thailand.
Keywords: Anopheles barbirostris; Malaria vector; Species complex; Sri Lanka